Smart Textiles: Smart Textile‐Based Personal Thermal Comfort Systems: Current Status and Potential Solutions (Adv. Mater. Technol. 5/2020). Issue 5 (11th May 2020) - Tabor, Jordan; Chatterjee, Kony; Ghosh, Tushar K.
Abstract : Clothing is intimately linked to human comfort. In article number 1901155, Tushar K. Ghosh and co‐workers first outline the issues fundamental to thermophysiological comfort and then explore the promise of the emerging field of textile‐based temperature and moisture sensors, thermal and moisture responsive actuators, and heating/cooling devices, that can take advantage of the internet of things and machine learning to provide a personal thermal environment.